CONCEPTUALIZATION OF THE MODEL FOR INNOVATIVE DEVELOPMENT OF THE ECONOMY OF UKRAINE IN THE CONTEXT OF DECENTRALIZATION - А. Kotelenets; N. Datsii; N. Filipova; O. Petryk; H. Kaplenko (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The article proposes scientific and methodological provisions for formation of the management model for innovative development of the economy of Ukraine on the basis of the general concept of socio-economic systems, taking into consideration the prerequisites and principles of a single system for implementing the goals of the model. Such a model includes the concept of innovative development, innovation strategies, innovation policy, and the mechanisms for innovative development management. It has been established that the formation of an effective management model of innovative development of the economy of Ukraine on the basis of adaptability and ability to provide a synergistic effect is possible provided striking the balance between the components with different potentials with a focus on natural potential. It has been identified the criteria for assessing the effectiveness of the management model for innovative development of the economy of Ukraine, which characterize the achievement by the country of a certain level of equipment and technology, the level of economic growth, welfare, and health of the population, intellectualization of society, environmental and economic security, etc. Further stages of decentralization in Ukraine and its impact on the economic development have been identified as follows: 1) deconcentration of power and resources; 2) adherence to the principles of the devolution of power; 3) power and resources will be distributed between traditional public authorities (state and self-governing) and market and public structures; 4) introduction of the newest models of public management of the economy. The priority tasks and features of the management model for innovative development of the economy of Ukraine in the context of decentralization are: 1) need to conduct research that will promote the use of opportunities for the progressive development of genetic research, combining an effective management system and technologies that complement the relevant achievements of genetics; 2) reducing the time for funding research, adapting the positive experience of highly developed countries; 3) formation of organizational and institutional structure aimed at simplifying the process of formation and implementation of economic innovations in Ukraine.